Empirical Shear Force Capacity And Stiffness Model Of The Cross-Formation Screw Connections In Timber– Concrete Composite Structures - Zahir, Mohd Khairul Akmal Md (Universiti Sains Malaysia, 2022)
The connection between the two materials has a significant impact on the stiffness and shear force capacity of Timber Concrete Composite (TCC) structures when they are in flexure. Due to some shortcomings in Eurocode 5 (EC5) and existing predictive strength and slip modulus models of screw connections, this work was undertaken. The failure to take into account the local characteristics of the screw embedded within the concrete on the behaviour of the connection between the timber and concrete is one flaw in these models. Additionally, while Eurocode 5 currently provides guidance for determining the shear force capacity of connections made of timber and timber, there is no similar guidance for connections made of wood and concrete. The current stiffness and shear force capacity model has been reinvestigated. It was discovered that no research had been done on creating a shear force capacity and stiffness model based on an X-formation screw and taking different screw angles between 0° and 90° into consideration. In this thesis, Multiple Linear Regression (MLR) analysis was used to create new shear force capacity and stiffness model. A set of 64 data from the previous research was used to compare the new shear force capacity and stiffness model with model from Gelfi et al., 2002), (Moshiri et al., 2014) and (Symons et al., 2010. After analysing the distance of plastic hinge from the interface between concrete and timber, lc and screw diameter, D were identified as parameters that influenced shear force. For stiffness there was no parameter that influenced the stiffness. The new empirical shear force capacity obtained was